1988
DOI: 10.1037/0278-6133.7.5.461
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, caffeine, and stress: Effects on blood pressure and heart rate in male and female college students.

Abstract: This study examined the independent and joint effects of cigarette smoking and caffeine consumption on blood pressure (BP) and heart rate (HR) reactions to stress in male and female college students. Following an initial physiological baseline, participants received one of four experimental treatments (paced smoking, caffeine, smoking plus caffeine, or neither) and had BP and HR measured before, during, and after two stressful tasks. The results revealed that, compared with the control condition, caffeine inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
2

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 25 publications
1
15
1
2
Order By: Relevance
“…METHODS Subjects The sample consisted of 15 healthy, non--smoking volunteers (12 male, three female) who had recreational resistance training experience, were non--hypertensive (SBP and DBP lower than 140/90 mmHg, respectively), had no orthopedic problems, and used no substances or medications with cardiovascular effects. Post--resistance exercise hypotension (Queiroz et al, 2013) and cardiovascular response related to caffeine intake (MacDougall, Musante, Castillo, & Acevedo, 1988) are similar in men and women. All subjects were light caffeine habituated (<250 ml of black coffee by day) (Noordzij et al 2005).…”
Section: Introductionmentioning
confidence: 71%
“…METHODS Subjects The sample consisted of 15 healthy, non--smoking volunteers (12 male, three female) who had recreational resistance training experience, were non--hypertensive (SBP and DBP lower than 140/90 mmHg, respectively), had no orthopedic problems, and used no substances or medications with cardiovascular effects. Post--resistance exercise hypotension (Queiroz et al, 2013) and cardiovascular response related to caffeine intake (MacDougall, Musante, Castillo, & Acevedo, 1988) are similar in men and women. All subjects were light caffeine habituated (<250 ml of black coffee by day) (Noordzij et al 2005).…”
Section: Introductionmentioning
confidence: 71%
“…Some studies have shown that caffeine and mental stress produce additive increments in blood pressure (1-5, 7. 8,13) or heart rate (4) in both caffeine users and nonusers, while others have reported synergistic effects on blood pressure, heart rate, forearm blood flow or neuroendocrine variables (2,3,6,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 96%
“…Most previous studies in both abstainers and regular users looked at combined effects of a single acute dose of caffeine and stress after an overnight period of abstinence (1)(2)(3)(4)(5)(6)(7)(8)(14)(15)(16)(17). This corresponds to taking measurements at the time of the day when the pressor effect of caffeine is at its maximum.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, in empirical studies, nicotine administration decreased body weight in humans and rats (Grunberg, 1982;Winders & Grunberg, 1989), decreased aggression in humans (Cherek, 1981;Cherek et aI., 1991) and in rats (Silvennan, 1971;ScheufeJe, 1997), and altered biochemical and behavioral responses to stress in rats (Benwell & Balfour, 1982;Cam & Bassett, 1983;1984;Sharp, Beyer, Levine, Morley, & McAllen. 1987;Peck, Dilsaver, & McGee, 1991;Acri, 1992Acri, , 1994Takada, Thara, Vrano, & Takada, 1995) and in humans (MacDougall, Musante, Castillo, & Acevedo, 1988;Gilbert, Robinson, Chamberlin, & Spielberger, 1989;Pomerleau & Pomerleau, 1990;Levin, Rose, Behm, & Caskey, 1991;Smits, Temme, & Thien, 1993).…”
Section: ) Effects Of Nicotinementioning
confidence: 99%